PENGUATAN KETERAMPILAN DIGITAL MELALUI PELATIHAN PEMBUATAN LANDING PAGE WEB DI SMK NEGERI 1 BONE - A. Najiah Nurul Afifah; Andi Asvin Mahersatillah Suradi (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2025)
Relevant digital skills to the needs of the modern professional world are the concern of SMK Negeri 1 Bone to prepare students to face competition in the digital era, especially web development. This community service activities were carried out through training to master the basics of web programming and the development of attractive and functional responsive designs through the creation of landing pages. The method of implementing activities is in the form of theoretical learning, intensive practice, and project-based evaluation. Participants create landing pages that were judged based on creativity, functionality, and design aesthetics. The results of this training showed that several groups of participants can implement interactive landing page features. Students were able to present the results of their work by explaining the design decisions and integrated functions to the instructor and other participants. This success provides a significant moral boost, strengthening confidence in developing a website. The trainees received certificates and the three best participants received awards in the form of coaching funds. This training is a strategic step to integrate digital skills into vocational education, answer the challenges of the ever-evolving job market, and prepare students to compete in the digital era. Therefore, future training should be more effective by increasing time allocation, collaborating with the technology industry, and expanding training materials with advanced topics in web development.